Perlindungan Hukum Bagi Pelaku Usaha Terhadap Pencabutan Izin Reklamasi Oleh Pemerintah Daerah - Inigo Putera Bagus Juwono (2020)
Availability lands in Indonesia doesn’t get along with growth citizen in Indonesia. The government is giving a solution to the building of the reclamation, but under the construction of the reclamation always inflict variety of problems. Permission cancellation for reclamation is action legal by government in order to annulment permission for its reclamation, government should pay attention in aspect of: authority, procedure and substantion. Besides, annulment permission reclamation by government based on legislation and principle general a good government. A legal form of legal protection by receiving authorization of reclamation In this case, the businessman or developers do administrative efforts and filing suit to civil court of justice. If there are parties that are affected with the verdict, can file an appeal to civil court of justice, it can be even comitted cassation law to supreme court of Indonesia